Digital Divide and e-Training for people with Disabilities - Hamburg, Ileana; Lütgen, Gabriela (Advances in Social Sciences Research Journal, 2018)
There are currently a number of challenges particularly for people with disabilities due to digital divide with a significant limitation of the ICT to be accessible and to adapt to user needs. This paper focusses on accessible ICT platforms and e-training as well as hopes and challenges of them. Cerebral palsy (CP), one of the most common motor disability in rehabilitation with antenatal antecedents and often multi-factorial is given as an example as well as a European project with the participation of authors as partners.